ACCESS OF THE CRIMINAL LAWSUIT PARTIES TO THE CASE FILE AT THE PRELIMINARY INVESTIGATION STAGE IN FRENCH LAW; A NEW STEP TOWARDS BALANCING OF RIGHTS (CAHIERS MAGELLANES-NS, 2024)
In spite of the fact that the confidentiality of the preliminary investigation plays a noteworthy role in discerning the truth and supporting the people involved in the criminal proceedings, the legislator has followed a moderate approach in the field of the preliminary investigation by emphasizing the suspect's right to defend himself; in such a way that the Balancing of the criminal lawsuit parties’ rights is guaranteed as much as possible. At present, the legislator, to support the efficiency of the preliminary investigation and the rights of the victim and to reduce the possible harmful effects caused by the suspect's knowledge of the details of the criminal case, has used mechanisms such as determining the papers and documents subject to access, postponing access to the case for a certain period, symmetry between the suspect and the complainant in benefiting from the right of access to the file. Likewise in present French law, for special crimes; as with organized and terrorist crimes and in cases of possible pressure on the victims or any other person who intervenes in the investigation, exceptional and distinct provisions have been considered. Since it aroused public opinion and citizens' emotions, it seems that “Outreau case”[1] has played a substantial role in the formation of these reforms. The current research, using the descriptive-analytical method and library sources and internet sites, inspects the degree of compliance with the regulations regarding access to the file with the principle of balancing the criminal lawsuit parties’ rights in the preliminary investigation stage in French law and it tries to analyze the relevant regulations to reveal its shortcomings and defects and provide appropriate suggestions.